Edge Stenosis After Covered Stenting for Long Superficial Femoral Artery Occlusive Disease: Risk Factor Analysis and Prevention With Drug-Coated Balloon Angioplasty. (June 2018) - Lin, Ting-Chao; Huang, Chun-Yang; Chen, Po-Lin; Lee, Chiu-Yang; Shih, Chun-Che; Chen, I-Ming
Purpose: To report a retrospective analysis of risk factors for edge restenosis after Viabahn stent-graft treatment of superficial femoral artery (SFA) occlusive disease and determine any protective effect of drug-coated balloons (DCBs) used at the time of stent-graft implantation.Methods: Between October 2011 and July 2016, 110 patients (mean age 73.3±7.6 years; 78 men) were treated with the Viabahn stent-graft for long SFA occlusions. Thirty-eight (34.5%) patients had DCB reinforcement at the distal edge of the stent-graft. For analysis, the population was divided into groups of no edge stenosis patients (n=88; mean lesion length 22.4±4.2 cm) and edge stenosis patients (n=22; mean lesion length 23.5±5.7 cm). The clinical outcomes, ankle-brachial indices, computed tomography angiography findings, and patency were compared at a minimum of 12 months. Logistic regression analysis was employed to determine risk factors for edge stenosis; the results are presented as the odds ratio (OR) and 95% confidence interval.Results: No differences in clinical or procedural characteristics were identified except the higher incidence of diabetes (p=0.008) and greater need for retrograde access (p=0.033) in the edge stenosis group. DCB reinforcement reduced the incidence of edge stenosis (p=0.021) and target lesion revascularization (TLR; p=0.010) and resulted in a significantly higher 1-year primary patency rate (92.1% vs 76.4%, p=0.042). However, multivariate analysis revealed only poor distal runoff (OR 0.31, 95% CI 0.11 to 0.83, p=0.020) as a predictor of edge stenosis.Conclusion: The risk of edge stenosis after Viabahn implantation was higher in patients with poor distal runoff. DCB reinforcement over the distal edge reduced edge stenosis, decreased 1-year TLR, and improved 1-year primary patency.